2017
DOI: 10.1377/hlthaff.2016.1344
|View full text |Cite
|
Sign up to set email alerts
|

Medicare Advantage Associated With More Racial Disparity Than Traditional Medicare For Hospital Readmissions

Abstract: We compared racial disparities in thirty-day readmissions between traditional Medicare and Medicare Advantage beneficiaries who underwent one of six major surgeries in New York State in 2013. We found that Medicare Advantage was associated with greater racial disparity, compared to traditional Medicare. After controlling for patient, hospital, and geographic characteristics in a propensity score based approach, we found that in traditional Medicare, black patients were 33 percent more likely than white patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 23 publications
4
33
1
Order By: Relevance
“…Medicare Advantage plans enroll higher proportions of racial/ethnic minorities and enrollees with lower income and education than the traditional Medicare program, and prior work has found substantial disparities in the quality of care in the MA program. [3][4][5][6][7][8][9][10][11][12][13][14] These disparities in care have been found within plans (disparities in quality of care for enrollees in the same plans), and between plans (disparities driven by disproportionate enrollment of minorities in plans with worse quality). 3,13,14 Since 2008, the US Centers for Medicare & Medicaid Services (CMS) has used a 5-star rating system to measure the performance of MA contracts and allocates $6 billion in annual bonus payments on the basis of these star ratings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicare Advantage plans enroll higher proportions of racial/ethnic minorities and enrollees with lower income and education than the traditional Medicare program, and prior work has found substantial disparities in the quality of care in the MA program. [3][4][5][6][7][8][9][10][11][12][13][14] These disparities in care have been found within plans (disparities in quality of care for enrollees in the same plans), and between plans (disparities driven by disproportionate enrollment of minorities in plans with worse quality). 3,13,14 Since 2008, the US Centers for Medicare & Medicaid Services (CMS) has used a 5-star rating system to measure the performance of MA contracts and allocates $6 billion in annual bonus payments on the basis of these star ratings.…”
Section: Introductionmentioning
confidence: 99%
“…Medicare Advantage plans enroll higher proportions of racial/ethnic minorities and enrollees with lower income and education than the traditional Medicare program, and prior work has found substantial disparities in the quality of care in the MA program. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 These disparities in care have been found within plans (disparities in quality of care for enrollees in the same plans), and between plans (disparities driven by disproportionate enrollment of minorities in plans with worse quality). 3 , 13 , 14…”
Section: Introductionmentioning
confidence: 99%
“…1 Multiple studies have shown racial disparities in hospitalizations, with African-Americans especially experiencing higher readmission rates for chronic conditions, including congestive heart failure, myocardial infarction, pulmonary disease, diabetes, and kidney disease. [2][3][4] Readmission disparities for African-Americans persist despite efforts to manage care and control costs with programs such as Medicare Advantage; one study notably demonstrated a 64% higher readmission rate for African-Americans postoperatively compared to Whites 5 . This inequity extends beyond hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…24 Similarly, a study of Medicare and Medicare Advantage patients in New York showed that black patients had a higher risk for readmission post-surgery discharge for coronary artery bypass graft than white patients. 32 …”
Section: Discussionmentioning
confidence: 99%